(untitled) (KULT_online, 2014)
In Der sympathische Vampir Marcus Recht describes fluid gender identities. He analyses the visual data of two main characters from the TV series "Buffy" and shows how spectators perceive both male characters as classically male on first sight, but a closer look reveals they are granted more leeway from binding gender roles. Using the series, Recht shows medial figures that broaden their gender identity and are able to change it. The analyzed characters give us examples of how we, too, are capable of more potential for movement within the areas of sexuality and gender.